Bottom-up perceptual salience and top-down retro-cues concurrently determine state in visual working memory. Issue 3 (March 2021) - Fan, Lingxia; Zhang, Lin; Diao, Liuting; Xu, Mengsi; Chen, Ruiyang; Zhang, Xuemin
Recent studies have demonstrated that in visual working memory (VWM), only items in an active state can guide attention. Further evidence has revealed that items with higher perceptual salience or items prioritised by a valid retro-cue in VWM tend to be in an active state. However, it is unclear which factor (perceptual salience or retro-cues) is more important for influencing the item state in VWM or whether the factors can act concurrently. Experiment 1 examined the role of perceptual salience by asking participants to hold two features with relatively different perceptual salience (colour vs. shape) in VWM while completing a visual search task. Guidance effects were found when either colour or both colour and shape in VWM matched one of the search distractors but not when shape matched. This demonstrated that the more salient feature in VWM can actively guide attention, while the less salient feature cannot. However, when shape in VWM was cued to be more relevant (prioritised) in Experiment 2, we found guidance effects in both colour-match and shape-match conditions. That is, both more salient but non-cued colour and less salient but cued shape could be active in VWM, such that attentional selection was affected by the matching colour or shape in the visual search task. This suggests that bottom-up perceptual salience and top-down retro-cues can jointly determine the active state in VWM.